Komunikasi Perubahan Sosial dan Jihad Literasi Pesantren : (Studi di Pondok Pesantren Kreatif Baitul Kilmah Bantul, Yogyakarta) - Abdul Halim; Tias Satrio Adhitama (Jurnal Ilmu Komunikasi, 2021)
This study examines the literacy jihad developed by Baitul Kilmah Creative Islamic Boarding School, Bantul, Yogyakarta. Literacy is not only a medium of learning and transfer of knowledge but also oriented as an agenda for the campaign of national ideology and resistance to achieve equality in cities and villages, as was done in Baitul Kilmah. Research type in this article is ethnoscience. The data collected are analyzed using political literacy theory. The results of the study show: first, Baitul Kilmah Creative Islamic Boarding School emphasizes that the struggle of students with literacy is a jihad, as is the teaching of jihad in Islam with its contemporary meaning. Second, the ideology promoted by Baitul Kilmah is a critical ideology that seeks to reconstruct the morale of the city which continues to experience degradation, and offers village civilization as an alternative solution. Third, this literacy jihad and campaign for social change is transformed into a village civilization. Fourth, the cultural base of rural communities is the spirit of literacy development in Baitul Kilmah. Fifth, the development of social change campaigns on important issues regarding the environment and nationality makes students the main actors.